Faktor-Faktor Yang Mempengaruhi Kelengkapan Rekam Medis Rawat Inap Dengan Menggunakan Diagram Fishbone di Rumah Sakit Pertamina Jaya Tahun 2017 - Siti Nadya Ulfa; Lily Widjaya (Indonesian of Health Information Management Journal (INOHIM), 2017)
AbstractAccording to the regulation minister of health No.269, 2008,medical record is a document containing records of patient identity, examination, and treatment. Medical records should be made and completed immediately after the patient receives health care. In Pertamina Jaya Hospital, in filing a medical record still can be found incompleteness. The purpose of this research are toconduct quantitative analysis of inpatient medical record and identify factors that influence the completeness of hospitalized medical record by using fishbone method.This research is using descriptive method and technique of collecting data by observation, interview, and literature study. Based on the result of research with observation on 56 inpatient medical records in May 2017, there were 74% medical records completeness. The factors influencing the completeness of medical record can be found by conducting observation and interview. There were some factors that affect the completeness of the medical record such as the insufficient time/busyto complete the medical record, unapplied sanction, lack of the socialization, the implementation of the medical record is not based on Standar Operasional Procedure, the form of quantitative analysis not covering all basic component, and limited funding for evaluation. As a solution to improve the completeness of the medical records, doing intensive socialization and creating reward &punishment system.Keywords: factors, completeness of inpatient medical record, fishboneAbstrakMenurut Permenkes Nomor 269 Tahun 2008, Rekam medis adalah dokumen yang berisikan catatan tentang identitas pasien, pemeriksaan, dan pengobatan pasien,rekam medisharus segera dibuat dan dilengkapi setelah pasien menerima pelayanan kesehatan. Di Rumah Sakit Pertamina Jaya dalam pengisian rekam medis masih ditemukan ketidaklengkapan. Tujuan dari penelitian ini adalahmelakukan analisis kuantitatif rekam medis rawat inapdan mengidentifikasi faktor-faktor yang mempengaruhi kelengkapan rekam medis rawat inap dengan menggunakan metode fishbone. Metode penelitian yang digunakan adalah dengan metode deskriptif dan teknik pengumpulan data dengan cara observasi, wawancara, dan studi kepustakaan. Berdasarkan hasil penelitian dengan melakukan observasi terhadap 56 rekam medis rawat inap pada bulan Mei 2017, ditemukan kelengkapan sebesar 74%. Dan faktor-faktor yang mempengaruhi kelengkapan rekam medis dapat ditemukan dengan melakukan observasi dan wawancara yaitu, waktu untuk melengkapi rekam medis tidak cukup/sibuk, tidak ada sanksi yang diterapkan, kurangnya sosialisasi, pelaksanaan pengisian rekam medis belum sesuai standar proseduroperasional, formulir analisis kuantitatif belum mencakup semua komponen dan pendanaan kelengkapan rekam medis terbatas. Maka disarankan untuk melakukan sosialisasi standar operasional prosedur secara intensif, dan pengadaan sistem reward dan punishment. Kata Kunci : faktor-faktor,  kelengkapan rekam medis rawat inap, fishboneone